Wybrane składowe obyczajowości seksualnej młodzieży. Poznawanie partnera = Selected components of youth`s sexual customs. Meeting a partner - Wąż, Krzysztof (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The transformation of sexual customs, especially in the case of teenagers, is one of the most dynamic phenomena observable in recent decades. In the literature, it is defined as the sexualization of young people, particularly of girls. Sexual customs are a complex category, on the one hand, including norms, patterns and models of activity related to sexual behaviors, manifestation and fulfillment of sexual needs (what is declared), and, on the other hand, concerning something that is real, observable in the activity of individuals, especially in the attitude towards the sexual partner.
Keywords: obyczajowość seksualna; młodzież; poznawanie partnera; sexual customs; youth; meeting a partner